The COVID-19 Pandemic Impact on Society: The Case of Digital Nomadism - Dimitrios VAGIANOS; Silja ENGEL (Communications of International Proceedings, 2023)
Since its outbreak, the Covid-19 pandemic has had a multifaceted impact on society. Public life was almost completely shut down, the future was uncertain and much took place within one's own four walls. Private travel was suddenly no longer possible, so that a longing for distant places arose. Jobs were moved to the home office as far as possible and companies had to upgrade their technical equipment to make this feasible. New technologies as well as the growing digitalization of companies, which was accelerated by the Covid-19 pandemic, made these new forms of work more popular and convenient. All of this led to frequent considerations about an alternative to the previous life, driven by the digital independence of the individual. In this article, the two individual areas of wanderlust and remote work are investigated through the lens of the pandemic implications, based mainly on German statistical data. Subsequently,   the digital nomadism perspective is outlined as a logical conformation of these two, proposing variables for models that can be used for analysis and forecasting of this innovative social trend.
Keywords: Covid-19 Pandemic; Digital Nomadism; Wanderlust; Teleworking; Digital Transformation